(untitled) (Web of Teachers: Inderscience Research, 2024)
This article explores the concept of speech strategies within the field of sociolinguistics. It defines speech strategies as the linguistic maneuvers employed by speakers to achieve communicative goals within specific social contexts and highlights their significance in revealing social meanings embedded within language use. The article examines key sociolinguistic factors influencing speech strategy selection, including social class, gender, age, ethnicity, and situational context. Specific examples of speech strategies, such as politeness strategies, indirectness, code-switching, accommodation, and hedging, are discussed. The article integrates perspectives from both Russian and English-speaking linguists to provide a richer understanding of speech strategies and addresses criticisms of the field while suggesting future research directions.